(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. La legge n. 40 sulla procreazione medicalmente assistita (pma) dopo gli interventi giurisprudenziali - 2. La pma per i singles e il presunto diritto alla mono-genitorialità - 3. Le scelte etiche del procreare di fronte ai nuovi ritrovati tecnologici - 4. La mediazione del (bio-)diritto laico. The alleged right to single parenthood and the ethical choices of beginning-life ABSTRACT: This contribution, taking its cue from requests for jurisprudential recognition of an alleged right to single parenthood, analyzes the phenomenon of pma for singles in the light of the different ethical conceptions of procreation, reaching the conclusion that the law 40 on pma should be entirely rewritten through a normative intervention oriented in the sense of a secular mediation, within the framework of the pluralism of ethical-religious conceptions present in society, which knows how to combine the right of self-determination with the duty of solidarity.